Baltské výpůjčky v sámštině - Hofírková, Lucie; Blažek; Václav (2011)
In the present article we summarize and evaluate both identified and hypothetical lexemes of Baltic origin in Saami, in a broader context of Fenno-Saamic and Fenno-Volgaic relations. Our conclusion is that c. 8 lexical correspondences between Baltic and Saamic from c. 40 Balto-Fenno- Saamic comparisons are without the Balto-Fennic counterparts. It means, it is probable that ancestors of Balts and ancestors of Saami were in a direct contact at least briefly. The contact territory could be sought in the south basin of the Finnish Bay and the river Neva.